Exploring the Lived Experiences of Street Homeless Persons in Johannesburg, South Africa - Emmison Muleya; Constance Matshidiso Lelaka; Johanna Kedibone Deka; Phumuzani Mpofu (Universitas Pattimura, 2026)
This study examines the lived experiences of individuals experiencing street homelessness in Johannesburg, South Africa, with a focus on the structural, social, and personal factors shaping their conditions. A qualitative approach using a descriptive phenomenological design was employed. Ten adult participants were recruited through purposive and snowball sampling. Data were collected using face-to-face semi-structured interviews and analysed thematically. The findings indicate that homelessness is driven by an interplay of family breakdown, unemployment, poverty, substance abuse, and relationship dissolution. Participants reported prolonged exposure to harsh living conditions, significant health challenges, limited access to healthcare, and frequent experiences of violence and exploitation. Structural barriers, particularly the lack of identification documents, further restricted access to essential government services. Survival strategies included recycling, begging, and transactional sex. Contrary to common assumptions, most participants were South African citizens rather than foreign nationals. This study highlights the agency and resilience of homeless individuals and underscores the need for integrated, trauma-informed, and rights-based interventions through multi-stakeholder collaboration to inform inclusive urban policies and sustainable social responses.